2021
DOI: 10.1504/ijpqm.2021.115290
|View full text |Cite
|
Sign up to set email alerts
|

Methodology of classification, forecast and prediction of healthcare providers accredited in high quality in Colombia

Abstract: This research presents a methodology for classification, forecasting and prediction of healthcare providers accredited in Colombia. For this purpose, a quantitative, descriptive and predictive analysis was carried out of 27 institutions accredited in Colombia by 2016. Consequently, the machine learning techniques cluster analysis and artificial neural networks were used to define business profiles of the institutions under study. The method classifying, forecasting and predicting the membership of a healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Samaneh Sheikh-Nia solved the same problem using standard and ensemble-based classification techniques. As mentioned in Section 2.1, many studies on the application of classification methods in determining the influence of different types of factors, from medical and social to economic, including both classification and prediction, could be found in the literature [45]. These methods were used in the diagnosis and prediction of the development of various diseases, such as breast cancer [46], HIV [47], and COVID-19 [48], but the authors have not found any application similar to the proposed generic methodology.…”
Section: Literature Review Of Different Methodologies That Deal With ...mentioning
confidence: 99%
“…Samaneh Sheikh-Nia solved the same problem using standard and ensemble-based classification techniques. As mentioned in Section 2.1, many studies on the application of classification methods in determining the influence of different types of factors, from medical and social to economic, including both classification and prediction, could be found in the literature [45]. These methods were used in the diagnosis and prediction of the development of various diseases, such as breast cancer [46], HIV [47], and COVID-19 [48], but the authors have not found any application similar to the proposed generic methodology.…”
Section: Literature Review Of Different Methodologies That Deal With ...mentioning
confidence: 99%
“…As we have already mentioned in the previous subchapter 2. 1 Literature review, in the literature we could find a lot of work that deals with the application of classification methods in determining the influence of different types of factors, from medical and social to economic, including, in addition to classification, forecasting and prediction [70]. F It could be also used in the diagnosis and prediction of the development of various diseases, such as breast 6 cancer in [71], HIV in [72], COVID19 in [73] etc.…”
Section: Literature Review Of the Application Of Classification Model...mentioning
confidence: 99%